실물옵션을 활용한 새만금 수상태양광 투자사업의 수익성 분석 - 김경석; Kim, Kyeongseok (한국건설관리학회 논문집, 22(1), 2021)
Saemangeum Development is the largest national project in South Korea, which has been developed for an agricultural, economic and tourist area for 30 years from 1987. In order to convert power sources that used to depend on nuclear and thermal power to eco-friendly for carbon reduction, the government plans to construct a 2.1GW floating photovoltaic project by investing 4.6 trillion won, as a public-private project. For success of the Saemangeum floating photovoltaic project, economic feasibility should be checked. This study defined the factors (construction cost, electricity selling price, power generation and maintenance cost) that give a effect to the volatility of the floating photovoltaic payoffs, and analyzed the volatility of payoffs during 20 years operation period. NPV and option value of the project were calculated by applying an option to abandon. According to NPV analysis, it is determined that projects are difficult to invest. But this project has economic feasibility through real options analysis. This study is expected to help decision-makers in the economic analysis of floating photovoltaic projects by using the real options analysis. 새만금개발은 1987년부터 30년간 정부가 농업, 경제와 관광지역으로 추진하고 있는 우리나라에서 가장 규모가 큰 국책사업이다. 우리나라는 원자력과 화력에 의존하던 전력원을 탄소저감을 위해서 친환경으로 전환하기 위해서 민관사업으로 우리나라 최대규모인 4.6조원을 투자하여 2.1GW의 수상태양광발전 프로젝트를 추진하고 있다. 새만금 수상태양광 프로젝트가 성공하려면 경제적 타당성을 확인해야 한다. 본 연구는 수상태양광사업의 변동성 요소들(건설비용, 전기판매가격, 발전량과 유지관리비용)을 정의하고, 20년간 운영하는 동안 수익의 변동성을 분석하였다. 불확실성으로 수익이 악화가 예상될 때 포기할 수 있는 권리를 가지는 포기옵션을 적용하여 프로젝트의 옵션가치를 구했다. NPV분석에 의하면 투자가 어려운 프로젝트가 옵션분석에 의하여 경제성을 확보할 수 있음을 확인하였다. 본 연구는 투자사업의 의사결정권자가 실물옵션분석방법을 활용하여 수상태양광프로젝트의 경제성분석에 불확실성을 고려할 수 있도록 도와줄 것으로 기대된다.